Nest predation and interspecific nesting associations involving plumbeous kite (ictinia plumbea) and becards (Pachyramphus spp.) - Bodrati, Alejandro (2017)
Interspecific nesting associations are among several strategies employed by birds to reduce the risk of nestpredation. Plumbeous Kites (Ictinia plumbea) aggressively defend their nest sites from potential predators, and participate in a little‐studied nesting association with various species of becards (Pachyramphus spp.). Here, we describe nesting associations involving Ictinia plumbea, other raptors, wasps, and becards, based on field observations from 1997 to 2016 in two ecoregions of Argentina, the Atlantic Forest and the Humid Chaco. We found 48% of Ictinia plumbea nests in close proximity to one or more becard nests. Kite nests were already active when becards began building. Green‐backed Becards (Pachyramphus viridis) were the most frequent associate, nesting 30?150 cm from active kite nests and sometimes appropriating their nest material. When potential predators came near their nests, becards appeared unable to drive them off, but their warning calls alerted the kites, which drove 13 species of potential nest predators away from kite‐becard nesting associations. Two kite nests ? both unaccompanied by becards ? were confirmed to have failed. At one, a Red‐breasted Toucan (Ramphastos dicolorus) captured the young kite nestling during a brief absence of both parents. We propose that (1) becards select nest sites near kites and benefit from the kites? aggressive nest defense, and (2) kites tolerate becards, possibly gaining a small advantage from their warning calls. We also found becards nesting beside five other species of raptors, and wasps. Network analysis revealed a higherdiversity of protective nesting associations in the Chaco than in the Atlantic Forest, but Ictinia plumbea and wasps were the most frequent nest associates of becards in both systems. Quantitative studies of nest‐site selection and nest survival in becards and kites are needed to reveal the behavioral mechanisms and fitness costs/benefits of this widespread interspecific nest association.